2021
DOI: 10.3390/jcm10061203
|View full text |Cite
|
Sign up to set email alerts
|

Factor XIII Activity Might Already Be Impaired before Veno-Venous ECMO in ARDS Patients: A Prospective, Observational Single-Center Cohort Study

Abstract: Direct complications in patients receiving extracorporeal (veno-venous) membrane oxygenation (vvECMO) are mainly either due to bleeding or thromboembolism. We aimed to evaluate the course of routine coagulation parameters and the activity of different coagulation factors—with special focus on factor XIII (F XIII)—before, during and after vvECMO in acute respiratory distress syndrome (ARDS) patients. The activity of coagulation factors and rotational thrombelastometry were analyzed in 20 ECMO patients before (T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…An analysis of the ELSO registry revealed a survival rate to discharge of 61% in trauma patients [ 200 ]. Extended advanced monitoring is suggested to detect early deterioration, ideally as a baseline before initiation of ECMO to prevent potentially deleterious bleeding or thromboembolic complications [ 201 , 202 ]. Using extracorporeal lung assist has been reported in various circuit compositions, with all of these reports describing feasibility without an increased risk of bleeding and survival benefits, as well as high survival rates [ 161 , 162 , 203 , 204 , 205 , 206 , 207 , 208 , 209 , 210 , 211 , 212 , 213 , 214 , 215 , 216 , 217 ].…”
Section: Factors Excluded As Contraindications/additional Contraindications Onlymentioning
confidence: 99%
“…An analysis of the ELSO registry revealed a survival rate to discharge of 61% in trauma patients [ 200 ]. Extended advanced monitoring is suggested to detect early deterioration, ideally as a baseline before initiation of ECMO to prevent potentially deleterious bleeding or thromboembolic complications [ 201 , 202 ]. Using extracorporeal lung assist has been reported in various circuit compositions, with all of these reports describing feasibility without an increased risk of bleeding and survival benefits, as well as high survival rates [ 161 , 162 , 203 , 204 , 205 , 206 , 207 , 208 , 209 , 210 , 211 , 212 , 213 , 214 , 215 , 216 , 217 ].…”
Section: Factors Excluded As Contraindications/additional Contraindications Onlymentioning
confidence: 99%
“…We also assessed the variables that could explain differences between POCT-APTT and lab-APTT and found that CRP, fibrinogen, factor XII levels, and LA positivity could explain differences between the two tests. Recent studies found that FXII and FXIII show a significant decrease during ECMO, FXIII even showing reduced levels hours before its initiation [ 39 , 40 ]. Low coagulation FXII activity has been associated with less thromboembolic complications [ 40 ], and was beneficial in an animal model, as its inhibition prevented fibrin deposition and thrombosis in the extracorporeal circuit [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent review has described three pools of FXIII within the circulation, in plasma, and within the cellular compartments of platelets and monocytes/macrophages, providing additional insights into the complex roles of FXIII in these physiological processes [78]. Although beyond the scope of this review, studies have indicated that FXIII levels/activity are impaired before and during extracorporeal membrane oxygenation [79][80][81]. Moreover, acquired coagulopathy and reduced FXIII levels have been reported in patients with COVID-19 [82][83][84].…”
Section: Future Directionsmentioning
confidence: 99%